Significant variations across European centres in implementing recommended guidelines for the paediatric gastroenterology endoscopy suite during the COVID-19 pandemic. Issue 3 (27th August 2021) - Athiana, Ilektra; Légeret, Corinne; Bontems, Patrick; Dall'Oglio, Luigi; De Angelis, Paola; Dias, Jorge Amil; Hauser, Bruno; Homan, Matjaž; Narula, Priya; Norsa, Lorenzo; Oliva, Salvatore; Papadopoulou, Alexandra; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) published recommendations regarding protection for the paediatric endoscopist during the coronavirus 2019 (COVID-19) pandemic.The aim of this survey was to investigate whether European paediatric gastroenterology centres applied the recommendations and how this extraordinary situation was handled by the different centres. Results: Twelve paediatric European gastroenterology centres participated. Nine centres (75%) screened their patients for possible COVID-19 infection before the procedure, the same amount of hospitals changed their practice based on the ESPGHAN recommendations. Six-seven percentage of the centres reduced the staff in the endoscopy suite, 83% of the units used FFP2/3 masks and protective goggles during the procedure and 75% wore waterproof gowns. Conclusion: Uniform guidelines could not be applied by all European hospitals at a certain time point of the viral spread, as different regions of Europe were not only affected differently by COVID-19, but also had different access to personal protective equipment.